Innovating Means of Payment in Chile, 1840s-1860 - Ross-Orellana, C (Palgrave Macmillan, 2016)
The post-independence economic vitality in Chile created conditions for innovation in the field of payments. Some attempts to create tickets (informal emissions) by business houses were quickly banned. Until then, the dominant idea was to devise means of payment only as coins minted in metal, such as gold, silver, copper and alloys. Despite this prohibition, the demand for means of payment in the 1840s increased along with the growth of the economy. Only in 1860, with the creation of the General Banking Law, were banks allowed to print their own money. With this development, the possibility of innovation in issuing payment methods was developed. © The Author(s) 2016.